Bilingualism in Contemporary Finland: Whither Swedish? - Embleton, Sheila (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1999)
Bishop Henry of Uppsala led an expedition to Finland in the 12th century, beginning the strong connection of Finland to Sweden, which has since undergone various metamorphoses, Sweden ruled Finland until 1809, when Finland became a Grand Duchy of Russia. Finland's degree of autonomy varied over the years, until Finnish independence in 1917. An 1863 decree provided that Swedish would remain an official language, but that Finnish would gradually be introduced into all domains, becoming fully official by 1883. Currently Finland is officially bilingual, with complex rules as to what services must be provided in which languages in which communes. The official high status of Swedish masks some striking demographic, practical, and sociopolitical realities. The percentage of Swedish speakers has fallen rapidly over the years (now about 5%), and, coupled with the fact that Finnish Swedish has many dialects (all highly divergent from standard Swedish), this has led to practical consequences (to be detailed), which have in turn further diminished the role, status, and number of speakers. Recent developments in culture (internationalization, communications, etc.) and politics (decline in importance of the Nordic Council, sudden rise in importance of the European Community, rapid changes in eastern Europe, rise of other minorities, etc.) have combined to significantly boost the position and importance of English, and, as I will argue in this paper, concomitantly to weaken the position of Swedish dramatically, official bilingualism and rhetoric to the contrary.